The Marseille caper [large type] - Mayle, Peter (Mayle, Peter. Sam Levitt mysteries., 2012)
When the immensely wealthy Francis Reboul asks Sam Levitt to take a job in Marseille, it's impossible for Sam and Elena Morales to resist the possibility of adventure - to say nothing of the pleasures of the region. Soon the two are enjoying sunshine, wine and bouillabaisse. But as a competition over Marseille's valuable waterfront grows more hotly disputed, Sam, representing Reboul, finds himself in the middle of an intrigue-ridden and dangerous real estate grab